Pneumatosis intestinalis post steroid use in a patient with immune-related adverse events: Case report, literature review and FAERS analysis - Zhang, Tingting; Cao, Mingnan; Zhao, Bin; Pan, Chen; Lin, Li; Tang, Chuanhao; Zhao, Zhigang; Duan, Jingli; Wang, Li; Liang, Jun (Frontiers in Pharmacology, 2023)
Introduction: The accurate diagnosis of pneumatosis intestinalis (PI) is increasing despite patients' limited identification of etiologic factors. Recently a patient with lung squamous carcinoma who developed PI following methylprednisolone administration for immune-related adverse events was treated at our hospital. Subsequent a literature review and an analysis of the FDA Adverse Event Reporting System (FAERS) database enabled the identification of additional cases of PI. Methods: A literature review of the MEDLINE/PubMed and Web of Science Core Collection databases using standard PI search terms to identify published cases of immune checkpoint inhibitors (ICIs) or steroids causing PI were performed. A separate retrospective pharmacovigilance study of FAERS enabled the extraction of unpublished cases of PI between the first quarter of 2005 and the third quarter of 2022. Disproportionality and Bayesian analyses were performed to identify signal detection in reported odds ratios, proportional reporting ratios, information components, and empirical Bayesian geometric means. Results: Ten case reports of steroid-related PI were retrieved from six published studies. The implicated drug therapies included pre-treatment with steroids before chemotherapy, combination therapy with cytotoxic agents and steroids, and monotherapy with steroids. In the FAERS pharmacovigilance study, 1272 cases of ICIs or steroid-related PI were incidentally reported. The signal detected in five kinds of ICIs and six kinds of steroids implied a positive correlation between the drugs and adverse events. Conclusion: Steroids might be the etiologic factors in the current case of PI. Reports supporting the role of steroids in suspected cases of PI can be found in literature databases and the FAERS database. Even so, as documented in FAERS, ICIs-induced PI should not be excluded.